UPAYA PEMENUHAN GIZI TAMBAHAN PADA ANAK MELALUI PELATIHAN PEMBUATAN NUGET AYAM KELOR DAN STICK DAUN KELOR DI DUSUN PANGENYAR KECAMATAN SUMBAWA - Ana Merdekawaty; Fatmawati; Ardiyansyah (Jurnal Pengabdian Masyarakat Waradin, 2021)
The purpose of this service activity is to increase the knowledge and skills of participants in Moringa processing; increase participants' knowledge about the potential of Moringa leaves as a healthy food ingredient, and produce Moringa chicken nuget products and Moringa leaf sticks. The activity method used is mentoring with activity stages; 1. preparation, 2. implementation, 3. evaluation. The results of the activity showed an increase in the knowledge and skills of the participants in processing Moringa leaves, participants knew that Moringa leaves have good nutritional potential and can be developed as a healthy food processing ingredient, and participants are skilled in processing Moringa leaves into Moringa chicken nuggets and Moringa leaf sticks. . Given the large benefits of this activity, it is advisable to carry out further activities in the form of assistance in marketing Moringa leaf processed products in order to increase people's income.